KOMUNIKASI KELOMPOK DAN KESEJAHTERAAN SOSIAL (Studi Deskriptif Kualitatif Tentang Komunikasi Kelompok Karang Taruna Mekar Remaja dalam Meningkatkan Kesejahteraan Sosial di Dusun Grasak Kismoyoso Boyolali) - Djaya, Tika Ristia (KOMUNITAS, 2013)
The objectives of the research are to study about group communication which are conducted by the members of ââMekar Remajaââ youth association and to know about the roles of its members inÂ  improvingÂ  socialÂ  welfare.Â  ThisÂ  researchÂ  usedÂ  descriptiveÂ  andÂ  qualitativeÂ  methodÂ  toÂ  explain about various phenomena that occur in the field. The location of this research is in Grasak village Kismoyoso Boyolali, the data of this research wereÂ  gained by doing interview, observation, and documentation. Sampel of this data are four membersof ââMekar Remajaââ youth association and two people who are not members of this association.The result of analysis which is conducted by the writer are: group communication which are conducted by ââMekar Remajaââ youth association isÂ  two ways communications that are: face to faceÂ  communication,Â  andÂ  communicationÂ  throughÂ  media (handÂ  phoneÂ  andÂ  invitation)Â  and conducting regular meeting every 35 days, this event has been effective. Another activities which areÂ  heldÂ  byÂ  ââMekarÂ  RemajaââÂ  youthÂ  associationÂ  such as:Â  entrepreneurship,Â  communityÂ  service, âsinomanâ, sport activities, ââhalal bi halal, ââIdul Adhaââ, and held many events to celebrate the independenceÂ  day.Â  MembersÂ  ofÂ  ââMekarÂ  RemajaââÂ  youth associationÂ  canÂ  maintainÂ  theÂ  group communicationÂ  whichÂ  isÂ  alreadyÂ  effective,Â  andÂ  improveÂ  theÂ  entrepreneurÂ  activitiesÂ  andÂ  other positive activities in order to increase the socialwelfare in Grasak village Kismoyoso Boyolali.